2006
DOI: 10.1158/1078-0432.ccr-06-0111
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 Promoter SNP309 Is Associated with the Risk of Hepatocellular Carcinoma in Patients with Chronic Hepatitis C

Abstract: Purpose: A single nucleotide polymorphism (SNP) in the promoter region of MDM2 gene, SNP309, has recently been shown to be associated with accelerated tumor formation in both hereditary and sporadic cancers in humans. However, the association of SNP309 with hepatocellular carcinoma is unknown. We evaluated the association of SNP309 with the risk of hepatocellular carcinoma development among Japanese patients with chronic hepatitis C virus infection. Experimental Design: We genotyped the SNP309 at the MDM2 prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
74
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 48 publications
(37 reference statements)
11
74
3
Order By: Relevance
“…Because of lack of healthy control samples in corresponding ethnic groups or countries, we were not able to test this hypothesis with a case-control study. However, in a recent study, Dharel et al reported that SNP309 is associated with the presence of hepatocellular carcinoma in Japanese patients with chronic hepatitis C [22]. In concordance with the study by Dharel et al, two recent studies indicated an association between the G genotype and risk for hepatocellular carcinoma in Moroccan and Korean patients with chronic hepatitis B infections [23,24].…”
Section: Discussionmentioning
confidence: 56%
“…Because of lack of healthy control samples in corresponding ethnic groups or countries, we were not able to test this hypothesis with a case-control study. However, in a recent study, Dharel et al reported that SNP309 is associated with the presence of hepatocellular carcinoma in Japanese patients with chronic hepatitis C [22]. In concordance with the study by Dharel et al, two recent studies indicated an association between the G genotype and risk for hepatocellular carcinoma in Moroccan and Korean patients with chronic hepatitis B infections [23,24].…”
Section: Discussionmentioning
confidence: 56%
“…This hypothesis has been supported by the work on MDM2 SNP309. As the initial publication (Bond et al, 2004), multiple studies have shown that the G-allele of MDM2 SNP309 is associated with the attenuation of the p53 pathway and an enhanced early onset of and increased risk for, tumorigenesis (Bougeard et al, 2006;Hong et al, 2005;Swinney et al, 2005;Allazzouzi et al, 2006;Bond et al, 2006a, b;Dharel et al, 2006;Lind et al, 2006;Menin et al, 2006;Ohmiya et al, 2006;Park et al, 2006;Ruijs et al, 2007;Zhang et al, 2006). Because modest changes in levels of other central nodes of the p53 pathway (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…As previously proposed, it is likely that individuals with inherently different levels of p53 function will respond differently to such environmental stresses and have different levels of risk for developing the associated cancers (Bond et al, 2005a). Three recent studies have provided evidence that this could be the case (Hong et al, 2005;Zhang et al, 2006;Dharel et al, 2006). DNA damage is just one form of genotoxic stress that cells undergo when exposed to smoke (DeMarini, 2004).…”
Section: Stresses Such As Smoking and Chronic Hcv Infectionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the cell model, the MDM2 SNP309G/G genotype shows elevated MDM2 transcription and expression, resulting in attenuation of the p53 pathway and accelerating tumor formation (Bond et al, 2004). It has been reported that the association of MDM2 SNP309 with various cancers and the correlation between MDM2 expression with poor prognosis (Hirata et al, 2007;Cescon et al, 2009;Toffoli et al, 2009); however, the association of MDM2 SNP309 with HCC is inconsistent between studies (Dharel et al, 2006;Yoon et al, 2008;Leu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%